Long-term Intake of Pasta Containing Barley (1–3)Beta-D-Glucan Increases Neovascularization-mediated Cardioprotection through Endothelial Upregulation of Vascular Endothelial Growth Factor and Parkin. Issue 1 (December 2017) - Casieri, Valentina; Matteucci, Marco; Cavallini, Claudia; Torti, Milena; Torelli, Michele; Lionetti, Vincenzo
Abstract Barley (1–3)β-D-Glucan (BBG) enhances angiogenesis. Since pasta is very effective in providing a BBG-enriched diet, we hypothesized that the intake of pasta containing 3% BBG (P-BBG) induces neovascularization-mediated cardioprotection. Healthy adult male C57BL/6 mice fed P-BBG (n = 15) or wheat pasta (Control, n = 15) for five-weeks showed normal glucose tolerance and cardiac function. With a food intake similar to the Control, P-BBG mice showed a 109% survival rate (P < 0.01 vs. Control) after cardiac ischemia (30 min)/reperfusion (60 min) injury. Left ventricular (LV) anion superoxide production and infarct size in P-BBG mice were reduced by 62 and 35% (P < 0.0001 vs. Control), respectively. The capillary and arteriolar density of P-BBG hearts were respectively increased by 12 and 18% (P < 0.05 vs. Control). Compared to the Control group, the VEGF expression in P-BBG hearts was increased by 87.7% (P < 0.05); while, the p53 and Parkin expression was significantly increased by 125% and cleaved caspase-3 levels were reduced by 33% in P-BBG mice.In vitro, BBG was required to induce VEGF, p53 and Parkin expression in human umbelical vascular endothelial cells. Moreover, the BBG-induced Parkin expression was not affected by pifithrin-α (10 uM/7days), a p53 inhibitor. In conclusion, long-term dietary supplementation with P-BBG confers post-ischemic cardioprotection through endothelial upregulation of VEGF and Parkin.